“SLOGA” – JOURNAL OF THE SERBIAN ORTHODOX PARISH OF THE HOLY TRANSFIGURATION OF THE LORD IN DESKA: BIBLIOGRAPHY APPENDIX OF THE JOURNAL (Heritage, 2023)
This paper deals with the journal published by the Serbian Orthodox Parish of the Holy Transfiguration of the Lord in Deska, a village near Szeged, where Serbs were once a majority but are now a small community that strives to preserve its language, culture, and customs through educational, cultural, and spiritual institutions. The journal "Sloga" was published for a brief period of nine years and besides religious topics, it contained texts dedicated to the community in the settlements of Deska, Vasharhelj, and Novi Sentivan, as well as profiles of parishioners with their detailed biographies. These data provide insights into the present life of the small community and the way of life of the small national group over the past few decades through the stories of the parishioners. This is also the first journal published in the Serbian language in villages in Hungary where the Serbian population was once the majority. It represents an extraordinary effort by the parish priest who organized the journal to preserve the language and maintain the unity of the community through information about its individual members.
Keywords: Periodical, journal